COMPENSATION FOR DAMAGES CAUSED BY A MOTOR VEHICLE OF FOREIGN REGISTRATION - Krulj - Mladenović, Milica (BizInfo Blace, 2019)
Accelerating the dynamics of everyday life and business, lead to a sudden increase in traffic accidents with an element of foreign countries and to the need to create specific rules for such specific situations. For this reason, the national legislation of most European countries obligatory insurance extends to vehicles of foreign registration, in order to make the protection of damaged persons as complete as possible. Many laws provide for damages to injured parties, regardless of whether they are damaged by a vehicle of domestic or foreign registration.